Music between nature and culture - Bielawski, Ludwik (Interdisciplinary Studies in Musicology, 2018)
In considering the titular opposition - music between nature and culture - we shall refer to such categories as time, with its levels and zones, and cultural communication. Conceptions of time. In an archaic situation dating from the Palaeolithic era, people lived, and cultures functioned, in sacred time, with no notion o f secular time. Another conception of time comes from the Bible, where we first encounter a ‘straightening’ of time, delineating its direction from the Creation to the Final Judgment (inopposition to ancient views on time, associating it with the wheel, with circular motion, dying and birth). Aristotle drew on Plato’s concept of time. He reduced it to the dimension of the human world, thereby initiating reflection on the ‘present’, which would endure in European thought through Saint Augustine to Edmund Husserl and our contemporary times. From this perspective, music is a process: playing, listening or participating in a musical event. Levels of time. These are as follows: atemporality (contains only simultaneity), prototemporality (contains temporal order, but also simultaneity), eotemporality (besides the features belonging to the aforementioned levels, also contains temporal intervals), biotemporality (as above, and also the present), and finally nootemporality (the human mind, awareness of time). The zones of time, meanwhile, comprise the zone of the psychological present (the motion of one’s own body, the perception of the sensory organs, natural language, musical language), the zone of performances of works (the shaping of form, including musical form), the zone of the temporal environment (three cycles: the diurnal, lunar and annual), and the zone of individual and communal life (the time from birth to death, and also memory, which reveals the sense of music from many perspectives). Cultural communication. In considering this phenomenon, we develop Roman Jakobson’s popular model of communication, expanded to encompass Karl Popper’s model of ‘three worlds’, through which we can propose a layered model of reality and, derived from that model, a concept of music as an efflorescence of nature in the culture of man. This is presented in detail in a series of figures (19-23 and especially 27).